PENDUGAAN STOK LOBSTER PAKISTAN (Panulirus polyphagus) DI KAWASAN PANTAI DESA SEBUBUS KECAMATAN PALOH KABUPATEN SAMBAS - Rosikin Rosikin; Widadi Padmarsari Soetignya; Sri Rahayu (Fakultas Pertanian Universitas Tanjungpura, 2020)
One of the fisheries commodities that are currently the mainstay of Indonesia's exports is lobster ( Panulirus spp ). Lobster is a very potential fishery product, because lobster has a high selling value and high nutrition. This research was conducted for four months, from December 2019 to March 2020 and the object under study was the pakistani lobster (Panulirus polyphagus).This research was conducted to estimate pakistani lobster stock in the beach area of Sebubus Village, Paloh District, Sambas Regency. Based on the results of the research, the ratio of male to female sex was 2.1: 1. The relationship between length and weight produces a negative allometric growth pattern. The growth rates of male and female Pakistani lobsters were 103.95 mm and 98.4 mm. The growth coefficient of male and female lobsters is 0.51 per year and 1.01 per year. Natural mortality of male and female lobsters is 0.66 per year and 1.05 per year and lobster mortality is caused by natural mortality factors. The exploitation rates for male and female lobsters are -0.13 per year and 0.39 per year, so the exploitation of lobsters is under fishing because the E value is below 0.5. The pattern of recruitment in male lobsters has one peak, namely in March and in females there are three peaks, namely in Juli, September and October.